2019
DOI: 10.1016/j.ccell.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

DNA Hypermethylation Encroachment at CpG Island Borders in Cancer Is Predisposed by H3K4 Monomethylation Patterns

Abstract: Highlights d Promoter CpG islands display asymmetric border methylation encroachment in cancer d 5hmC is enriched in normal cells at CpG island shores prone to methylation spread d H3K4me1 patterns at CpG island borders are associated with the mode of encroachment d H3K4me1 disruption results in DNA methylation alterations at island borders

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 87 publications
13
44
0
1
Order By: Relevance
“…Consistent with these findings, we found 5hmC enrichment among introns, enhancers, and regions with transcriptionally active chromatin. Furthermore, we observe a depletion of high 5hmC loci among CpG island regions, while an enrichment at CpG island shore regions, consistent with previous findings [8,24], as well as models suggesting the presence of 5hmC at CpG island shore regions prevents methylation encroachment of promoter CpG islands in cancer [30]. Consistent with prior studies, We also observe significant enrichment of high 5hmC CpGs among CpG island shelf and open sea regions [8,24].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with these findings, we found 5hmC enrichment among introns, enhancers, and regions with transcriptionally active chromatin. Furthermore, we observe a depletion of high 5hmC loci among CpG island regions, while an enrichment at CpG island shore regions, consistent with previous findings [8,24], as well as models suggesting the presence of 5hmC at CpG island shore regions prevents methylation encroachment of promoter CpG islands in cancer [30]. Consistent with prior studies, We also observe significant enrichment of high 5hmC CpGs among CpG island shelf and open sea regions [8,24].…”
Section: Discussionsupporting
confidence: 92%
“…Substantial deviation from DNA methylation patterns in normal breast tissue has been observed in premalignant lesions as well as in advanced disease [36,37]. Although 5hmC tends to be depleted in proliferating cells [27,28], recent studies have suggested 5hmC may be involved in the regulation of cancerrelated phenotypes [30,43,54,55]. To assess the potential contribution of 5hmC to breast carcinogenesis, we utilized available data describing regulatory regions present in variant human mammary epithelial cells (vHMECs), proliferative clones of HMECs that invariably result during cell culture, and share several phenotypes with premalignant breast cancers.…”
Section: Normal Breast Tissue 5hmc Is Enriched Among Genomic Regions mentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this model, in a mouse model of BrafV600E-driven colon cancer, escape from senescence and tumor progression was linked to increased expression of Dnmt3b and methylation and silencing of p16 (Carragher et al, 2010). According to this model, although activated BRAFV600E can increase the selective pressure that favors CIMP, methylation is not directly caused by BRAFV600E but has an inherent tendency to encroach on unmethylated CpG islands during aging (Skvortsova et al, 2019;Ushijima and Suzuki, 2019;Tao et al, 2019). In another model that more directly links oncogenic signaling and CIMP, it has been proposed that BRAFV600E signaling recruits DNMT3B to genes silenced by CIMP via the transcriptional repressor, MAFG, thereby directly promoting CIMP (Fang et al, 2014(Fang et al, , 2016.…”
Section: Introductionsupporting
confidence: 52%
“…Similarly, promoter hypermethylation of tumor suppressor genes has also been considered a common and driving event in breast malignancies. Loss-of-function mutations in DNA hydroxylases ( TET1 , TET2 and TET3 ) or overexpression of DNA methyltransferases ( DNMT1 , DNMT3A and DNMT3B ) 26,27 , and recently tumor hypoxia 28 have been reported to be associated with aberrant DNA methylation, yet the molecular origin of promoter hypermethylation in breast cancer remains obscure 27,29 .…”
Section: Introductionmentioning
confidence: 99%